Organic Sampah Organik Desa Pandan Dulang Kecamatan Semidang Aji dengan Teknologi Biodigester - Ferry Desromi; yuliantini eka putri; Lindawati Lindawati; Rachmi Layina Chimayati; Hasmawaty Hasmawaty (Jurnal Nusantara Mengabdi, 2022)
Purpose: to analyze the potential of organic waste using a digester test kit (Biogas Reactor). With a biogas reactor fermentation test equipment, 250 liter plastic drum, biogas volume can be known for 15-26 days. The anaerobic process is carried out by observing and analyzing the biogas reactor to produce biogas. gas and electricity and can reduce waste problems that often arise in the community, And one step in realizing the preservation of natural resources and improving human welfare by creating environmental conservation. Methodology/approach: This activity is carried out using the Biodigester method using a drum.   Results/findings: from processing organic waste with a certain ratio and Producing gas equivalent to 3 kg of gas, which can be applied in Pandan Dulang village. Conclusion: This activity can motivate villagers to be able to manage organic waste with biodigester technology using drums.